The length of price&reimbursement negotiation procedures in Italy in the period 2021-2023 was independent from the price of medicines - Raffaella Cocciolo; Paola Turella; Daniela Pilunni; Pierluigi Navarra (Global & Regional Health Technology Assessment)
Background: The duration of price&reimbursement (P&R) procedures is taken as a key performance indicator of Regulatory Agencies in Europe. In this study we have tested the hypothesis that the price of medicines may have negatively affected the duration of P&R negotiations in Italy in the period 2021-2023.